(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the Kochkar Norkobil’s stories “We did not return from the war” and “Weeping behind the river”, about suffering from Afghan war, which reflect the life of the “lost generation”. The consequences of the senseless war, downfall of the younger generation, the political system of that period have been studied